Unleashing the potential of dance: a neuroplasticity-based approach bridging from older adults to Parkinson’s disease patients - Meulenberg, Cécil J. W.; Rehfeld, Kathrin; Jovanović, Saša; Marusic, Uros (Frontiers in Aging Neuroscience, 2023)
Parkinson's disease (PD) is a neurodegenerative disorder that affects >1% of individuals worldwide and is manifested by motor symptoms such as tremor, rigidity, and bradykinesia, as well as nonmotor symptoms such as cognitive impairment and depression. Non-pharmacological interventions, such as dance therapy, are becoming increasingly popular as complementary therapies for PD, in addition to pharmacological treatments that are currently widely available. Dance as a sensorimotor activity stimulates multiple layers of the neural system, including those involved in motor planning and execution, sensory integration, and cognitive processing. Dance interventions have been associated with increased activation of the prefrontal cortex, as well as enhanced functional connectivity between the basal ganglia, cerebellum and prefrontal cortex. Overall, the evidence suggests that dance interventions can induce neuroplastic changes in PD patients, leading to improvements in both motor and cognitive functions, although the literature on dance-induced neuroplasticity in PD is sparse. This review highlights the potential of dance therapy as a non-pharmacological intervention in PD and offers insights into the potential mechanisms underlying its efficacy. Further research is warranted to determine the optimal dance style, intensity, and duration for maximum therapeutic benefit and to determine the long-term effects of dance intervention on PD progression.